2021
DOI: 10.32861/ijwpds.72.21.26
|View full text |Cite
|
Sign up to set email alerts
|

Health Implications of Air Quality Index of Fine and Coarse Particulates During Outdoor Combustion of Biomass in the Niger Delta, Nigeria

Abstract: Rural dwellers in the Niger Delta commonly use biomass for cooking and other activities. This study investigated the air quality index of fine particulate matter 2.5 (PM2.5) and coarse particulate matter 10 (PM10) and its health implications during outdoor combustion of fuelwood in the Niger Delta, Nigeria. A mini-volume air sampler (model: AEROCET 531) was used to measure PM2.5, PM10, and total suspended particulate (TSP) in the study area. A bimonthly triplicate sampling was carried out at 3 distances in 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 3 publications
0
0
0
Order By: Relevance
“…This is in agreement with previous works in the Niger Delta particularly in Bayelsa, Rivers, Delta and Abia states. Richard et al [17], reported PM 2.5 and PM 10 in the range of 26.44 -40.10 µg/m 3 and 81.63 -141.51µg/m 3 due to the waste dump in some regions in Rivers, Bayelsa, Delta and Abia state. Richard et al [18], reported PM 2.5 and PM 10 in the range of 19.85 -27.95 µg/m 3 and 55.66-80.59 µg/m 3 due to the combustion of biomass in some regions in Rivers, Bayelsa, Delta and Abia state.…”
Section: Discussionmentioning
confidence: 98%
“…This is in agreement with previous works in the Niger Delta particularly in Bayelsa, Rivers, Delta and Abia states. Richard et al [17], reported PM 2.5 and PM 10 in the range of 26.44 -40.10 µg/m 3 and 81.63 -141.51µg/m 3 due to the waste dump in some regions in Rivers, Bayelsa, Delta and Abia state. Richard et al [18], reported PM 2.5 and PM 10 in the range of 19.85 -27.95 µg/m 3 and 55.66-80.59 µg/m 3 due to the combustion of biomass in some regions in Rivers, Bayelsa, Delta and Abia state.…”
Section: Discussionmentioning
confidence: 98%